The Utility of the Marshmallow Barium Swallow Esophagogram for Investigation of Ineffective Esophageal Motility: A Systematic and Narrative Review - Wilson, H.; Mocanu, V.; Wong, C.; Karmali, S. (Journal of Gastrointestinal and Abdominal Radiology, 2022)
Objectives Current gold standard investigations to determine the pathology of ineffective esophageal motility (IEM) are invasive and resource-intensive. Marshmallow barium swallow esophagogram (MBSE) is emerging as a more feasible modality; however, our understanding of its role in the clinical setting is limited. Our aim was to appraise the current literature and describe the effectiveness and limitations of MBSE as a potential diagnostic tool when investigating the pathological cause of IEM.Methods A search in PubMed was conducted on May 23, 2021. Search terms included “marshmallow” AND “barium.” We included all studies which examined MBSE in the context of esophageal disease. The primary outcome of interest was to characterize the use of MBSE in current literature.Results A total of 12 studies were retrieved after initial search with 9 studies meeting final inclusion criteria. A total of 375 patients were included, with 296 patients (79%) having a relevant diagnosis or symptom prompting investigation with MBSE. The most common diagnoses included referral to a gastroenterology clinic for a barium swallow (44%), post-Angelchik insertion (23%), and dysphagia (13%). Esophageal disease was identified in both the MBSE and other screening tests in 63% participants, whereas in 27% participants abnormalities were only seen using the MBSE.Conclusion There is currently limited high-quality evidence on the use of MBSE to diagnose IEM. Further large-scale studies comparing its use in patients with different pathologic causes of IEM and of older age are required to further delineate the optimal delivery of this emerging diagnostic modality.
Keywords: marshmallow; barium swallow; esophageal motility; dysphagia